THE EFFECT OF REGIONAL VARIATION OF LATTICE PREFERRED ORIENTATION ON SURFACE WAVEFORMS - Oda H.; Onishi S. (My University, 2001)
We investigate the effect of the lateral variation of seismic anisotropy on long-period surface waves, calculating synthetic seismograms for earth models with azimuthal anisotropy whose hexagonal symmetry axes are horizontally oriented in the depth range between the Moho discontinuity and 420 km depth. The following anisotropic earth models are examined. In the first model, the hexagonal symmetry axes are uniformly oriented. In the second model, the azimuth, ξ, of the symmetry axis changes according to ξ = nθ, where n and θ are a positive integer and the colatitude, respectively. In the third model, the seismic anisotropy is the same as that of the first model but the anisotropic region is restricted in a given range of colatitude. For all anisotropic earth models, a quasi-Love wave commonly appears as a wave packet prior to the Rayleigh wave arrival on the vertical- and radial-component seismograms. In the first earth model, the quasi-Love wave is strongly excited when the ray path of the surface wave obliquely crosses the symmetry axes. An anomalously large spectral amplitude, which is caused by toroidal-spheroidal coupling associated with the azimuthal anisotropy, is found at frequencies lower than 4 mHz. The second earth model shows that as the lateral variation of axis orientation becomes rougher, the spectral amplitude anomaly is seen at higher frequencies and thus the quasi-Love waveform becomes high frequency. The surface wave synthetics calculated for azimuthal anisotropy whose axis orientation varies laterally with very short wavelength exhibit a transversely isotropic characteristic. In the third earth model, if the surface wave arrives at a station after travelling into an anisotropic region, then the quasi-Love wave is observed irrespective of whether the observation station is located in an anisotropic or an isotropic region. The quasi-Love wave is effectively generated by Love-to-Rayleigh conversion in the vicinity of the boundary between isotropic and anisotropic regions.
Keywords: AZIMUTHAL ANISOTROPY; FREE OSCILLATIONS; LATERAL HETEROGENEITY; SURFACE WAVES; SYNTHETIC SEISMOGRAMS